Implementing Interoperability in the Seafood Industry: Learning from Experiences in Other Sectors. (August 2017) - Bhatt, Tejas; Gooch, Martin; Dent, Benjamin; Sylvia, Gilbert
Abstract: Interoperability of communication and information technologies within and between businesses operating along supply chains is being pursued and implemented in numerous industries worldwide to increase the efficiency and effectiveness of operations. The desire for greater interoperability is also driven by the need to reduce business risk through more informed management decisions. Interoperability is achieved by the development of a technology architecture that guides the design and implementation of communication systems existing within individual businesses and between businesses comprising the supply chain. Technology architectures are developed through a purposeful dialogue about why the architecture is required, the benefits and opportunities that the architecture offers the industry, and how the architecture will translate into practical results. An assessment of how the finance, travel, and health industries and a sector of the food industry—fresh produce—have implemented interoperability was conducted to identify lessons learned that can aid the development of interoperability in the seafood industry. The findings include identification of the need for strong, effective governance during the establishment and operation of an interoperability initiative to ensure the existence of common protocols and standards. The resulting insights were distilled into a series of principles for enabling syntactic and semantic interoperability in any industry, which we summarize in this article. Categorized as "structural, " "operational, " and "integrative, " the principles describe requirements and solutions that are pivotal to enabling businesses to create and capture value from full chain interoperability. The principles are also fundamental to allowing governments and advocacy groups to use traceability for public good.